Neuronal Ensembles Organize Activity to Generate Contextual Memory - Marks, William D.; Yokose, Jun; Kitamura, Takashi; Ogawa, Sachie K. (Frontiers in Behavioral Neuroscience, 2022)
Contextual learning is a critical component of episodic memory and important for living in any environment. Context can be described as the attributes of a location that are not the location itself. This includes a variety of nonspatial information that can be derived from sensory systems (sounds, smells, lighting, etc.) and internal state. In this review, we first address how the contextual information works for remembering specific episodes, in particular focusing on contextual fear conditioning paradigm. We then discuss the current knowledge on the underlying neural circuitry in the entorhinal cortex - hippocampus (EC-HPC) network. We next discuss the physiological processes that underlie contextual representations in the EC-HPC network, focusing on the role of ensemble activity as a representation of context by the description of remapping, and demonstrate recent finding of context specific neural ensemble. We further discuss the circuit mechanisms for the formation and retrieval of remote contextual memory. Finally, we consider factors external to the EC-HPC network and their role in the determination of contextual memory.